PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN: PROFITABILITAS SEBAGAI VARIABEL MODERATING - Putra, Andhika Permana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to observe the influence of the Corporate Social Responsibility (CSR) to the companyâs value with profitability as the moderating variable for the Manufacturer Companies listed in Indonesia Stock Exchange (IDX) during the period of 2010 â 2012.The research samples which consist of 25 manufacturer companies which are listed in Indonesia Stock Exchange (IDX) with the number of observations are 75 and they are selected by using purposive sampling. The audit financial report data and the annual report obtained from Indo-Exchange File (IDX). The hypothesis test in this research is using multiple linear regressions analysis to test the influence of Corporate Social Responsibility (CSR) to the companyâs value with profitability as the moderating variable. In this research, the Corporate Social Responsibility (CSR) variable is measured by using corporate social disclosure (CSD) variable, profitability is measured by using Return on Equity (ROE), and the companyâs value is using Tobinâs Q.The research result by using multiple linear regression shows that Corporate Social Responsibility (CSR) has influenced to the companyâs value. On the other hand, the moderating variable analysis is using the interaction test method of Moderated Regressions Analysis (MRA) shows that the profitability is moderating the influence of Corporate Social Responsibility (CSR) to the companyâs value.Keywords: Corporate Social Responsibility, Profitability, Companyâs Value